FORMATION OF ENVIRONMENTAL COMPETENCE OF FUTURE NURSES IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT OF SOCIETY (Innovative professional education, 2024)
The problem formation of environmental competence of future nurses in the conditions of sustainable development of society is considered. The importance of solving this issue in the context of environmental protection and opportunities for improving theenvironmental situation, awareness of future nurses’ sense of involvement in environmental problems and responsibility for results of their actions and deeds in the interests of personal ecological safety of the environment, timely resolution of urgent environmental safety issues for their patients, is outlined, which will provide an opportunity to overcome the environmental crisis in the future. This is very important during the period of recovery of the country after the end of martial law.
Keywords: environment, ecological competence, future nurses, sustainable development, professional college